The Comparison of Sanai and Rumi's Outlooks Towards Women - Fereshteh Arjmandi; Ahmadreza Keikhafarzaneh; Mostafa Salari (هنر اسلامی, 2020)
The position and prominence of women in any society is associated to the attitude of the time and individuals towards women. The place of women in Iranian society has always has been controversial. In the meantime, the works of poets can be a mirror for understanding the situation of women. By considering the fact that the worldview of every poet, writer, or thinker is influenced by the intellectual, social, and cultural memory of the time and place in which the person exists; Sanai and Rumi are prominent Iranian poets whose works reflect the political, social and cultural conditions of their life. The issue raised in this study is the transformation of the position of women in society during the time of the mentioned poets. This research is accomplished by a descriptive and analytical method and relies on library data. Findings show that from the Sanai to Rumi periods, a unique social and cultural change took place that led to the enhancement of the status of women and this has been effective in the depiction of women's personalities. Sanai has a mainly negative and critical view of women and rarely cares about her position as a mother and in the service of her religious attitude towards women; nonetheless, Rumi considers woman as a manifestation of divine beauty; furthermore, in Rumi's poetry, woman is the soul, earth, and essence, and she complements creation and this distinguishes the manner in which the female figure is depicted in the poetry of Sanai. Research aims: 1. Corresponding the image of a woman in the poems of Sanai and Rumi. 2. Analysis of effective factors in drawing the image of women in the period of Sanai and Rumi. Research questions: 1. What are the differences between the female image in the poems of Sanai and Rumi? 2. What factors were involved in drawing the image of women in the period of Sanai and Rumi?